Friend or Foe? The Varied Faces of Homeostatic Synaptic Plasticity in Neurodegenerative Disease - Taylor, Henry B. C.; Jeans, Alexander F. (Frontiers in Cellular Neuroscience, 2021)
Homeostatic synaptic plasticity (HSP) regulates synaptic strength both pre- and postsynaptically to ensure stability and efficient information transfer in neural networks. A number of neurological diseases have been associated with deficits in HSP, particularly diseases characterised by episodic network instability such as migraine and epilepsy. Recently, it has become apparent that HSP also plays a role in many neurodegenerative diseases. In this mini review, we present an overview of the evidence linking HSP to each of the major neurodegenerative diseases, finding that HSP changes in each disease appear to belong to one of three broad functional categories: 1. deficits in HSP at degenerating synapses that contribute to pathogenesis or progression; 2. HSP induced in a heterosynaptic or cell non-autonomous manner to support the function of networks of which the degenerating synapses or cells are part; 3. induction of HSP within the degenerating population of synapses to preserve function and to resist the impact of synapse loss. Understanding the varied manifestations of HSP in neurodegeneration will not only aid understanding mechanisms of disease but could also inspire much-needed novel approaches to therapy.